2009
DOI: 10.1007/s10570-009-9351-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cationization on adsorption of silver nanoparticles on cotton surfaces and its antibacterial activity

Abstract: Cotton was cationized by exhaustion method using 3-chloro-2-hydroxypropyl trimethyl ammonium chloride (CHPTAC) as a cation-generating agent. Adsorption of silver nanoparticles on normal and cationized cotton was studied by exhaustion method at temperatures of 80°C and 100°C. Two exhaustion baths were used, containing nanosilver colloidal solutions stabilized by two different stabilizers and various concentrations of silver nanoparticles. Fourier-transform infrared (FT-IR) spectra of normal and cationized sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(74 citation statements)
references
References 41 publications
(44 reference statements)
0
72
0
1
Order By: Relevance
“…Silver particles dispersed in aqueous solutions usually have a negative surface charge (Jones 2002;Shateri Khalil-Abad et al 2009) and then create a repulsive force against the cellulose fibers, which inhibits the sedimentation of silver particles on the surface of the fibers. Consequently, silver particle adsorption is much lower on normal cotton than on nitrogen-plasma-treated cotton fibers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silver particles dispersed in aqueous solutions usually have a negative surface charge (Jones 2002;Shateri Khalil-Abad et al 2009) and then create a repulsive force against the cellulose fibers, which inhibits the sedimentation of silver particles on the surface of the fibers. Consequently, silver particle adsorption is much lower on normal cotton than on nitrogen-plasma-treated cotton fibers.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the addition of chitosan to the CM-cellulose can increase the crosslinking degree and the adsorption capacity of the blend of hydrogels (Zhao and Mitomo 2008). In other research, it was shown that the cationization process using 3-chloro-2-hydroxypropyl trimethyl ammonium chloride (CHPTAC) on cotton fabric caused an increase in the absorption of nanosilver particles on the surface (Shateri Khalil-Abad et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of the fabric was tested qualitatively and quantitatively by the disk diffusion method 10,11,20 and reduction of colony forming units (CFU) 16,21,22 of Escherichia coli (Gram-negative bacterium). For disk diffusion method, a mixture of nutrient broth and nutrient agar in 1 L distilled water at pH 7.2 as well as the empty Petri plates were autoclaved.…”
Section: Microbial Experimentationmentioning
confidence: 99%
“…Many methods have been reported, such as fluorocarbon repellent finish, chemical binding of heterocyclic N halamine functional group to polyamide, using plasma, or immobilization of antimicrobial metallic nanoparticles on textiles (TiO 2 , Ag, Cu, ZnO, etc.) [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%